Penerapan Model Flipped Classroom Berbantuan Short Video Tips and Trick untuk Meningkatkan Kemampuan Pemecahan Masalah - Syafa'atin, Nur; Arifin, Zaenal; Haryono, Heny Ekawati (Papanda, 2025)
This study aims to identify the differences in mathematical problem-solving abilities between students taught using the Flipped Classroom learning model with the aid of Short Video Tips and Tricks media and students taught using the conventional learning model. This research uses a quantitative approach. The type of research that has been used is a quasi-experiment. The research sample consisted of 62 students from the 10th grade at SMK NU 1 Karanggeneng, comprising 31 students in the experimental group and 31 students in the control group. The sampling for this research was conducted using the Cluster Random Sampling technique. The instrument used in this study is a test instrument in the form of a pretest and posttest to measure students' mathematical problem-solving abilities. Data analysis was conducted by applying the t-test with prerequisite tests including normality and homogeneity tests. The t-test data analysis yielded significant results (sig 2-tailed) <0.001. Considering the significance value is lower than 0.05, it can be stated that there is a significant difference between the two groups. This indicates that the Flipped Classroom learning model supported by Short Video Tips and Tricks media effectively improves students mathematical problem-solving abilities.